2012
DOI: 10.4184/asj.2012.6.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Decompression and Shortening Reconstruction with a Titanium Mesh Cage through a Posterior Approach Alone for the Treatment of Lumbar Burst Fractures

Abstract: Study DesignA retrospective study.PurposeTo examine the efficacy and safety for a posterior-approach circumferential decompression and shortening reconstruction with a titanium mesh cage for lumbar burst fractures.Overview of LiteratureSurgical decompression and reconstruction for severely unstable lumbar burst fractures requires an anterior or combined anteroposterior approach. Furthermore, anterior instrumentation for the lower lumbar is restricted through the presence of major vessels.MethodsThree patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…Before surgery, 9 patients were graded as Frankel C and 10 were graded as Frankel D. All patients recovered >1 grade after surgery and all of them could walk with or without a cane at the time of discharge. Mean preoperative pain VAS score was 7.2 (range, [6][7][8][9]. Pain in the low back or legs was relieved in the early postoperative period for all patients, and the VAS score of each remained at a mean of 1.4 until final follow-up (range, 0-2).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Before surgery, 9 patients were graded as Frankel C and 10 were graded as Frankel D. All patients recovered >1 grade after surgery and all of them could walk with or without a cane at the time of discharge. Mean preoperative pain VAS score was 7.2 (range, [6][7][8][9]. Pain in the low back or legs was relieved in the early postoperative period for all patients, and the VAS score of each remained at a mean of 1.4 until final follow-up (range, 0-2).…”
Section: Resultsmentioning
confidence: 97%
“…5,6 We began performing posterior-approach vertebral replacement with a cylindrical cage for the treatment of thoracolumbar burst fracture and osteoporotic late vertebral collapse in 2004. 7 The clinical results were satisfactory; however, subsidence of the cage into the vertebrae was seen in several cases. Therefore, since 2005, we have been using a modified technique with large-sized rectangular parallelepiped cages (REC cages) to prevent subsidence.…”
mentioning
confidence: 93%
“…The question as to how these fractures should be approached and stabilised (anteriorly or posteriorly) has been the subject of debate. Some authors have confirmed that direct decompression of the middle column can be done through the posterior approach [13]. However, It is generally believed that canal decompression is limited by and often incomplete with the posterior approach when treating thoracolumbar fractures associated with neurologic deficit.…”
Section: Discussionmentioning
confidence: 98%
“…Neurologic deficit was caused by impact and compression to the ventral surface of the spinal cord in most patients with thoracolumbar fractures, and the anterior approach provided optimal direct exposure for visualisation of the ventral aspect of the dura mater during surgical decompression [1,14]. Such a procedure would offer patients with neurologic deficit a better chance of improving than when using other procedures, even though this technique is surgically more challenging and has a greater potential for complications [13].…”
Section: Discussionmentioning
confidence: 99%
“…Th e 10 articles -out of 33 -that met the criteria and were included in the fi nal database, discuss the most frequently employed surgical treatment methods for the thoracal and lumbar fractures: posterior short segment fi xation [10][11][12][13][14][15], on one hand, and anterior approach only, as well as posterior-anterior approach [16][17][18][19], on the other.…”
Section: Methodsmentioning
confidence: 99%